2001
DOI: 10.1128/jvi.75.5.2246-2252.2001
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Human Immunodeficiency Virus Type 1 IIIB to a Neutralization-Resistant Phenotype in an Accidentally Infected Laboratory Worker with a Progressive Clinical Course

Abstract: The role of humoral immunity in controlling human immunodeficiency virus type 1 (HIV-1) is still controversial. The resistance of primary HIV-1 variants to neutralization by antibodies, sera from HIV-1-infected patients, and soluble CD4 protein has been suggested to be a prerequisite for the virus to establish persistence in vivo. To further test this hypothesis, we studied the neutralization sensitivity of two IIIB/LAV variants that were isolated from a laboratory worker who accidentally was infected with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 65 publications
5
40
0
Order By: Relevance
“…SIV MAC Δvpr viruses rapidly revert to a WT version when injected in rhesus macaques (14). A similar reversion has been observed in a laboratory worker accidentally contaminated with a vpr-deficient strain of HIV-1 (15,16). Several studies also reported mutations in the vpr gene in long-term nonprogressor (LTNP) patients (17)(18)(19)(20).…”
mentioning
confidence: 57%
“…SIV MAC Δvpr viruses rapidly revert to a WT version when injected in rhesus macaques (14). A similar reversion has been observed in a laboratory worker accidentally contaminated with a vpr-deficient strain of HIV-1 (15,16). Several studies also reported mutations in the vpr gene in long-term nonprogressor (LTNP) patients (17)(18)(19)(20).…”
mentioning
confidence: 57%
“…Experiments on immune selection and changes in neutralization phenotypes in HIV-1-infected patients are generally complicated by the lack of knowledge of the infecting viral strain and time of infection and by the low levels of in vitro serum antibody neutralization characteristic of primary HIV-1 neutralization. However, a recent study did characterize the neutralization phenotypes of two HIV-1 IIIB variants that were isolated from a laboratory worker accidentally infected with the neutralization-sensitive HIV-1 IIIB strain (2). Compared to the original virus in the viral inoculum, the viral isolates displayed an increased resistance to neutralization over time.…”
Section: Discussionmentioning
confidence: 99%
“…With viruses isolated 4 years after the isolation of LW/C from the infected laboratory worker, a recent report suggests that env mutations in the in vivo revertants are involved in increased resistance to neutralizing antibodies and in AIDS development (4). Interestingly, the A-to-T mutation in the env V3 loop common to LW/C, HXB2/LW (40), and other isolates from the infected laboratory worker (27,44) is also associated with escape from antibody neutralization (10).…”
Section: Discussionmentioning
confidence: 99%